MODEL MEMBUDAYAKAN BUDAYA MEMBACA MELALUI BUKU ANAK-ANAK - Wati, Hera (LPPM STKIP PGRI Bandar Lampung, 2020)
Reading is the process of receiving information and knowledge for a better life. Reading habits should be formed by the environment. Village is the smallest environment of a country and it has a significant influence in formed a habits of their society. Cultivating Reading Culture is expected to be a good national character. The reading level of the Indonesian people is still very low and therefore a method is needed in cultivating a reading culture. Based on the other and prevous study reading motivation influences the culture of reading and reading habits. Therefor, it is crusial to find out model of teaching or motivate students or children’s to read. In order to follow up research on reading culture and support the government in finding methods to cultivate the reading culture of Indonesian people starting from remote area so that they are able to play an active role in releasing their backwardness, this research is carried out. This research was conducted in Lubuk Pauh Village, BTS ULU District, Musi Rawas Regency, South Sumatra. This study involved 206 village children who were under 15 years of age that randomly divided into two, the treatment group and the control group. Treatment is carried out for 16 meetings. The reading model by using children's books can improve children's reading culture in remote areas by looking at the enthusiasm of children and parents towards the implementation of activities.